(3TQM GdafGQi Ydi ebWYGJ YTQjf eNJQYI aj YTQjf YdekG dhGdOgs - (3eMeO Hf MeRI GdafGQj, TeS GdOjf ,J (B834 (3g` s
(3ChdgG (B:s
(3CeG HYO abO LQi SfI Gddg JYGdi ai GdCee efP Ndb GdYGde s
(3BNQgG (B:s
(3hGdMeO ddg Ydi Jhajb GdEJeGe hGdUdGI hGdSdGe Ydi SjOfG eMeO hYdi Bdg hUMHg GdcQGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs